A versatile δ-aminolevulinic acid (ΑLA)-cyclodextrin bimodal conjugate-prodrug for PDT applications with the help of intracellular chemistry - Aggelidou, Chrysie; Theodossiou, Theodossis A.; Gonçalves, Antonio Ricardo; Lampropoulou, Mariza; Yannakopoulou, Konstantina (Beilstein Journal of Organic Chemistry, 2014)
Grafting of δ-aminolevulinic acid (1) moieties on the narrow periphery of a β-cyclodextrin (β-CD) derivative through hydrolysable bonds was implemented, in order to generate a water-soluble, molecular/drug carrier with the capacity to undergo intracellular transformation into protoporphyrin IX (PpIX), an endogenous powerful photosensitizer for photodynamic therapy (PDT). The water-soluble derivative 2 was prepared by esterifying δ-azidolevulinic acid with heptakis(6-hydroxyethylamino-6-deoxy)-β-cyclodextrin, with an average degree of substitution, DS = 3. Delivery of water-soluble, colorless 2 to cells resulted in intense red fluorescence registered by confocal microscopy, evidently due to the engagement of the intracellular machinery towards formation of PpIX. Conjugate 2 was further complexed with a fluorescein-labeled model guest molecule which was successfully transported into the cells, thereby demonstrating the bimodal action of the derivative. The present work shows the versatility of CDs in smart applications and constitutes advancement to our previously shown PpIX-β-CD conjugation both in terms of water solubility and lack of aggregation.
Keywords: cyclodextrins; PDT; protoporphyrin IX; prodrug; δ-aminolevulinic acid

(untitled) - Dolmans, D. E. J. G. J.; Fukumura, D.; Jain, R. K. (Nat. Rev. Cancer, 2003)

(untitled) - Nemeth, A. M.; Russell, C. S.; Shemin, D. (J. Biol. Chem., 1957)

(untitled) - Kennedy, J. C.; Pottier, R. H. (J. Photochem. Photobiol., B: Biol., 1992)

(untitled) - Gauffier, J. M.; Berg, K.; Peng, Q.; Anholt, H.; Selbo, P. K.; Ma, L.-W.; Moan, J. (Cancer Res., 1997)

(untitled) - Vianna Lopez, R. F.; Lange, N.; Guy, R.; Lopes Badra Bentleya, M. V. (Adv. Drug Delivery Rev., 2004)

(untitled) - Aggelidou, C.; Theodossiou, T. A.; Yannakopoulou, K. (Photochem. Photobiol., 2013)

Cyclodextrin Technology - Szejtli, J. (Kluwer Academic, 1988)

(untitled) - Hunter, C. A.; Sanders, J. K. M. (J. Am. Chem. Soc., 1990)

(untitled) - Siggel, U.; Bindig, U.; Endisch, C.; Komatsu, T.; Tsuchida, E.; Voigt, J.; Fuhrhop, J.-H. (Ber. Bunsen-Ges. Phys. Chem., 1996)

(untitled) - Kano, K.; Fukuda, K.; Wakami, H.; Nishiyabu, R.; Pasternak, R. F. (J. Am. Chem. Soc., 2000)

(untitled) - Mourtzis, N.; Paravatou, M.; Mavridis, I. M.; Roberts, M. L.; Yannakopoulou, K. (Chem. – Eur. J., 2008)

(untitled) - Vizitiu, D.; Walkinshaw, C. S.; Gorin, B. I.; Thatcher, G. R. J. (J. Org. Chem., 1997)

(untitled) - Bunke, H.; Zerbe, O.; Schmid, H.; Burmeister, G.; Merkle, H. P.; Gander, B. (J. Pharm. Sci., 2000)

(untitled) - Vallinayagam, R.; Bertschy, H.; Berger, Y.; Wenger, V.; Neier, R. (Synthesis, 2007)

(untitled) - Tamm, C. (Pure Appl. Chem., 1992)

(untitled) - Gadelle, A.; Defaye, J. (Angew. Chem., Int. Ed. Engl., 1991)

(untitled) - Vallinayagam, R.; Weber, J.; Neier, R. (Org. Lett., 2008)

(untitled) - van den Akker, J. T.; Iani, V.; Star, W. M.; Sterenborg, H. J.; Moan, J. (Photochem. Photobiol., 2000)

Peroxidizing Herbicides - Krijt, J. (Peroxidizing Herbicides: Toxicology to Mammals and Non-target Organisms, 1999)

(untitled) - Zidovetzki, R.; Levitan, I. (Biochim. Biophys. Acta, 2007)

(untitled) - Theodossiou, T. A.; Yannakopoulou, K.; Aggelidou, C.; Hothersall, J. S. (Photochem. Photobiol., 2012)